Impedance and Modulus Spectroscopy Characterization of Tb modified Bi0.8A0.1Pb0.1Fe0.9Ti0.1O3 Ceramics - Thakur, Shweta; Rai, Radheshyam; Bdikin, Igor; Valente, Manuel Almeida (Materials research (São Carlos, São Paulo, Brazil), 2016)
In this paper we present the impedance spectroscopy of ternary solid solutions of BiFeO3, TbFeO3 and PbTiO3, prepared by solid-state reaction method. The preliminary structural studies were carried out by x-ray diffraction technique, showing the formation of polycrystalline sample with ABO3 type of perovskite structure with hexagonal symmetry for Bi0.8Tb0.1Pb0.1Fe0.9Ti0.1O3system at room temperature. Dielectric and impedance study of this ceramic has been characterized in the temperature range 175 - 325 0C and frequency range 100 Hz - 1 MHz. The maximum ferroelectric transition temperature (Tc) of this system was in the range 210 - 225 0C with the dielectric constant having maximum value ~2480 at 1 kHz. The complex impedance graph exhibited one impedance semicircle arc at all reported temperatures, which indicates that the impedance response is a Cole-Cole type relaxation. Single semicircle indicate that the grain effect of the bulk in ceramic. The bulk resistance of the material decreases with increasing temperature showing negative temperature showing a typical semiconducting property, i.e. negative temperature coefficient of resistance (NTCR) behavior.